Selective Attention Modulates the Nonlinear Interaction between Stimuli - YeeJoon Kim; Preeti Verghese (i-Perception, 2012)
Prior studies suggest that visual attention selects objects of interest by biasing the competition in favor of attended items. However, our current understanding of this competitive process is based on indirect inference. To fill this critical gap in our understanding of selective attention, we directly measured the interaction between two stimuli by using high-density EEG combined with cortical source localization. This technique offers a powerful approach to directly measure responses to individual stimuli (self-terms) as well as to their interaction (intermodulation term). Observers were tested with a pair of adjacent wedge-shaped gratings flickering at two different frequencies (7.14 Hz and 5.56 Hz, respectively), and two static wedge-shaped gratings located diametrically opposite the flickering wedges. By directing attention to one or both stimuli we determined how attention modulated the response to each stimulus as well as to the interaction between the two stimuli. These responses were compared to a condition when observers attended away from the flickering gratings. Our data show that selective attention differentially modulates self-terms as well as intermodulation terms. Consistent with data from previous single-cell studies, the self-terms have the greatest amplitude when attention is directed to one of the two stimuli. In contrast, the intermodulation term has the greatest amplitude when observers attend to both stimuli, is smaller when they attend to one grating, and insignificant when attention is directed away. Our results suggest that this interaction term is a valuable tool to advance our understanding of the non-linear processes involved in selective attention.